Titik Nadir Demokrasi Pasca Reformasi: Quo Vadis Civil Society - Shokheh, Mukhamad (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
The challenge after the 1998 reforms is the formation of a democratic society that has independence in the political and economic fields. Democracy cannot be realized in an atmosphere full of dependency, for this reason, all elements need to be involved in increasing their capacity as nation citizens. This article analyzes post-reform democratic life and efforts to form a democratic society after authoritarianism. Important research findings show that improving democratic life needs to be initiated by all elements. The encouragement to create a civil society movement to be involved in various areas of life is a sign that democratic life still needs to continue to be developed, whereas, in recent years, various challenges to democracy have given rise to a setback. , the nuances of repression are a characteristic that is quite visible, for this reason, to control the role of the authorities, civil society is needed, through community movements that have political and social awareness will give birth to a better quality of democracy. The conclusion of this article emphasizes the need for a political culture reform agenda from the ruling elements to the lower levels of society to create a smooth democratization process and reveal authoritative qualities and the need to prioritize humanist qualities in the nation.